2006
DOI: 10.1159/000095267
|View full text |Cite
|
Sign up to set email alerts
|

Assembly, Trafficking and Function of γ-Secretase

Abstract: γ-Secretase catalyzes the final cleavage of the β-amyloid precursor protein to generate amyloid-β peptide, the principal component of amyloid plaques in the brains of patients suffering from Alzheimer’s disease. Here, we review the identification of γ-secretase as a protease complex and its assembly and trafficking to its site(s) of cellular function. In reconstitution experiments, γ-secretase was found to be composed of four integral membrane proteins, presenilin (PS), nicastrin (NCT), PEN-2 and APH-1 that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 147 publications
2
115
0
2
Order By: Relevance
“…This apparent contradiction was coined the spatial paradox by Annaert and De Strooper (1999). Although still not resolved completely, the work of many labs now indicates that mature, proteolytically active PS/g-secretase is principally localized not in ER, Golgi, or postGolgi transport vesicles but rather at the PM and in the endosomal/lysosomal system, including phagosomes and autophagosomes (reviewed in Pasternak et al 2004;Kaether et al 2006a;Nixon 2007;Dries and Yu 2008). The g-secretase subunits found in the ER/early secretory pathway most likely represent unassembled or partially assembled subcomplexes, but not the active enzyme.…”
Section: Subcellular Sites Of G-secretase-mediated App Processingmentioning
confidence: 99%
“…This apparent contradiction was coined the spatial paradox by Annaert and De Strooper (1999). Although still not resolved completely, the work of many labs now indicates that mature, proteolytically active PS/g-secretase is principally localized not in ER, Golgi, or postGolgi transport vesicles but rather at the PM and in the endosomal/lysosomal system, including phagosomes and autophagosomes (reviewed in Pasternak et al 2004;Kaether et al 2006a;Nixon 2007;Dries and Yu 2008). The g-secretase subunits found in the ER/early secretory pathway most likely represent unassembled or partially assembled subcomplexes, but not the active enzyme.…”
Section: Subcellular Sites Of G-secretase-mediated App Processingmentioning
confidence: 99%
“…It has been argued that the presenilin complex could act at the cell surface (Kaether et al 2006) and this has always been somewhat at odds with observation that Psn resides somewhere in the endocytic pathway (Ray et al 1999, Pasternak et al 2003. The recent observations emphasize that accumulation of Notch in the endocytic pathway, probably in a post Rab5 and/orRab7 compartment, can lead to its activation via S3 cleavage.…”
Section: Notch Traffickingmentioning
confidence: 99%
“…The ability of the four components to form up to six distinct complexes suggests each may possess different substrate affinities and serve importance in specific environments. Some authors have also suggested that other proteins associated with the γ-secretase complex, like TMP21, may assist in determining the cleavage specificity of the enzyme with its substrates [87][88][89][90], further suggesting a physiological regulation of substrate recognition and target processing. Mutations in PS1 are responsible for over 50% of fAD cases and are highly penetrant before the age of 65 [88][89][90].…”
Section: S383mentioning
confidence: 99%
“…Some authors have also suggested that other proteins associated with the γ-secretase complex, like TMP21, may assist in determining the cleavage specificity of the enzyme with its substrates [87][88][89][90], further suggesting a physiological regulation of substrate recognition and target processing. Mutations in PS1 are responsible for over 50% of fAD cases and are highly penetrant before the age of 65 [88][89][90]. These PS mutations tend to shift the cleavage specificity of C99 to increase generation of Aβ 42 [91], possibly by altering γ-secretase conformation to decrease or increase binding of the enzyme with the Aβ residues responsible for forming Aβ 40 or Aβ 42 , respectively [92].…”
Section: S383mentioning
confidence: 99%